Language and cultural barriers. An approach to intercultural communication inside NGOS in Ayacucho - Guillen Miranda , Dayana Estefany (Tecnohumanismo, 2022)
This paper sought to analyze the existing linguistic and cultural barriers in intercultural communication within NGOs in Ayacucho. It was a quantitative investigation, a non-experimental - cross-sectional study. the Survey of the representative sample (35 people from 20 to 45 years old) was used. The instrument was the questionnaire, it has 80 items. Likewise, these questions are broken down into blocks, the first being on acculturation (1-26) linked to; then on multiculturalism (27 to 34), prejudice (35 to 42), intercultural sensitivity (43 to 70), sociocultural competence (71 to 80). After analized the results, was possible to conclude that, even with support, it is very limited and concrete actions are required to make possible the integration of the cultures at stake, both that of the resident.